LABOR MARKET IN UKRAINE: CURRENT STATE AND WAYS OF STABILIZATION (Economic journal of Lesya Ukrainka Volyn National University, 2023)
Introduction. The labor market is an important component of the country’s economic system, a kind of indicator of its state, as well as a reflection of the level of social development. Military actions on the territory of Ukraine, changes in the socio-economic situation necessary the development of a system of effective measures to stabilize the labor market in modern realities.The purpose of the article. The article aims is to research the current state of the labor market in Ukraine and to substantiate the ways of its stabilization.Results. General trends in the development of the domestic labor market in the pre-war period are determined. The main indicators characterizing the current state of the labor market are analyzed. The trends of their change during January-November 2022 are determined. Government initiatives that contributed to increasing the flexibility of the labor market, stimulating employment, and optimizing labor relations are considered. Two trends characteristic of the modern labor market are identified. In particular, the appearance of new vacancies in the western regions of Ukraine, which is the result of the relocation of business from the southern and eastern parts of the country and the increase in the number of unemployed in the front-line territories, as well as those where active hostilities are taking place. Possible ways of stabilizing the domestic labor market during martial law are substantiated. It is proposed to focus efforts on three areas: creation of favorable conditions for conducting business activities; ensuring the employment of the population and guaranteeing the appropriate level of wages; stabilization of the social and humanitarian situation and prevention of exacerbation of social tension in society.Conclusions. Today, the labor market of Ukraine are characterized by significant deformation, lack of parity between demand and supply, and a drop in the level of income of the population. Its stabilization is an extremely important task, given the emergence of various population groups affected by the armed conflict. In current realities, state regulation of the labor market is an important prerequisite for expanding employment opportunities and raising the standard of living standards of the population.
Keywords: labor market, employment, unemployment, temporarily displaced persons, migration, state initiatives.